Stimulating Gross Motor Skills In Deaf-Mute Children In A Special Needs Elementary School Via Games - Khairani, Khairani; Ungerer, Lazuardi Van; Helmi, Boby (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aimed to evaluate the effectiveness of structured game-based interventions in improving gross motor skills among deaf-mute children in a special needs elementary school setting. Materials and methods: A quasi-experimental study was conducted with 36 students (ages 7-12 years) from a special needs elementary school in Binjai city, North Sumatra. Participants were randomly divided into experimental (n=18) and control (n=18) groups. The experimental group received 12 weeks of structured game-based motor skill interventions (3 sessions/week, 45 minutes/session), while the control group continued regular physical education. Gross motor skills were assessed using the Test of Gross Motor Development-3 (TGMD-3) pre- and post-intervention. Results: Statistical analysis using SPSS v27 revealed significant improvements in the experimental group's gross motor skills. The experimental group showed significant increases in locomotor skills (pre: M=42.3, SD=6.8; post: M=58.7, SD=5.2; p<0.001) and ball skills (pre: M=38.9, SD=7.1; post: M=52.4, SD=6.3; p<0.001) compared to the control group. Conclusions: Game-based interventions significantly enhanced gross motor skills in deaf-mute children. These findings support the implementation of structured play-based programs in special needs education settings.